CircRNA-ceRNA Network Revealing the Potential Regulatory Roles of CircRNA in Alzheimer’s Disease Involved the cGMP-PKG Signal Pathway - Zhang, Yuan; Qian, Lili; Liu, Yingying; Liu, Ying; Yu, Wanpeng; Zhao, Yanfang (Frontiers in Molecular Neuroscience, 2021)
Background: Alzheimer's disease (AD) is a chronic progressive neurodegenerative disease. The characteristic pathologies include extracellular senile plaques formed by β-amyloid protein deposition, neurofibrillary tangles formed by hyperphosphorylation of tau protein, and neuronal loss with glial cell hyperplasia. Circular RNAs (circRNAs) are rich in miRNA-binding sites (miRNA response elements, MREs), which serve as miRNA sponges or competitive endogenous RNAs (ceRNAs). Although several research groups have identified dysregulated circRNAs in the cerebral cortex of SAMP8 mice or APP/PS1 mice using deep RNA-seq analysis, we need to further explore circRNA expression patterns, targets, functions and the signaling pathways involved in the pathogenesis of AD and in particular the hippocampal circRNA expression profiles in AD. Methods: We used deep RNA sequencing to investigate circRNA-ceRNA network patterns in the hippocampus of APP/PS1 mice. Results: In our study, 70 dysregulated circRNAs, 39 dysregulated miRNAs and 121 dysregulated mRNAs were identified between the APP/PS1 group and the wild-type group at 8 months in the hippocampus of the mice. Through correlation analysis, we identified 11 dysregulated circRNAs, 7 dysregulated miRNAs and 8 dysregulated mRNAs forming 16 relationships in the circRNA-miRNA-mRNA regulatory network. Gene ontology (GO) analysis indicated that the dysregulated circRNAs were most enriched in biological metabolic processes. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the dysregulation of circRNAs was enriched in the cGMP-PKG signaling pathway, cAMP signaling pathway, Hippo signaling pathway, platelet activation, long-term potentiation and axon guidance. In addition, our findings preliminarily verified that the novel_circ_0003012/mmu-miR-298-3p/Smoc2 signaling axis may regulate the pathophysiology of AD by affecting the cGMP-PKG signaling pathway. Conclusions: These newly identiﬁed circRNAs in networks and signaling pathways reveal potential diagnostic or therapeutic targets for AD.